Perceived Stress and Society-Wide Moral Judgment - Yi Chen; Junfei Lu; David I. Walker; Wenchao Ma; Andrea L. Glenn; Hyemin Han (European Journal of Investigation in Health, Psychology and Education, 2025)
This study examines the relationship between perceived stress and society-wide moral judgment by integrating two influential frameworks: the neo-Kohlbergian approach and the CNI model of utilitarian-deontological decision-making. The neo-Kohlbergian approach to moral judgment proposes three moral schemas: (1) Personal Interest (PI), where decisions are self-focused; (2) Maintaining Norms (MN), which emphasizes adherence to social rules and norms; and (3) Postconventional (PC), where universal ethical principles are prioritized. The CNI model for Utilitarian-Deontological judgment features three psychological processes in decision-making: Sensitivity to Consequence, Sensitivity to Norm, and Inaction Preference. A survey study was conducted to measure perceived stress, neo-Kohlbergian moral judgment (using the behavioral Defining Issues Test [DIT]), and the psychological processes underlying utilitarian-deontological decision-making (CNI). The results indicate that higher perceived stress is linked to greater PI schema endorsement, reduced Norm Sensitivity, and increased Consequence Sensitivity. Furthermore, the PI schema mediated the relationship between perceived stress and Norm Sensitivity. These findings provide insights into how stress shapes moral reasoning and decision-making, with implications for psychological and ethical studies.